Partisan Information Sources and Affective Polarization: Panel Analysis of the Mediating Role of Anger and Fear. (September 2019) - Lu, Yanqin; Lee, Jae Kook
Drawing on the 2012 American National Election Studies (ANES) panel data, this study explores the influence of the consumption of partisan information sources on affective polarization and investigates the mechanism underlying this relationship. The results show that exposure to pro-party television sources strengthens affective polarization among partisans. The polarizing effects of pro-party sources are mediated by the discrete negative emotions (i.e., anger and fear) toward presidential candidates. The study discusses the impact of selective exposure on deliberative and participatory democracies.